Physio-ogical-hygienic peculiarities of the labouramong the operators of the bottling of non-alcoholic and lowalcoholic beverages into the glass containers in modern manufacture (Environment & Health, 2015)
Objective. We presented a hygienic assessment of the effect of the harmful factors of the occupational environment, noise in particular, on the organisms of the operators of bottling of non-alcoholic and low alcoholic beverages on the basis of the study of the labour conditions and health state and substantiated the sanitary recommendations.Materials and Methods. Ourstudy was conducted at the "Rosinka" factory. We assessedthe following parameters: noise level, microclimate indices, illumination at the working places; heaviness and intensity of the operators' work. We determined a biological age of the personnel. Morbidity of the operators was analyzed by the periodical medical examinations' data.Results. The operatorsare undergone a complex effect of the occupational noise, unfavorable microclimate and insufficient level of the artificial and natural illumination. The basic harmful factor of the occupational environment is a noise with the levels exceeding the allowable values by 15.6 dBA. The labour conditions of the operators, according to hygienic normative 3.3.5-3.3.8; 6.6.1-083-2001, arereferred to the 3.2 danger group (harmful). We revealed a high morbidity level with the sensorineural deafness (16.02 ± 4.90)%, ocular diseases (53.40 ± 6.66)%, respiratory diseases (30.26 ± 6.13)%, disgestion diseases (8.90 ± 3.80)% among the workers of "noise" professions. We also detected the increased rates of the operators' aging. Conclusions. Acauseeffect relationship between conditions, character of labor and levels of morbidity, indices of the biological age of the operators was established in the study.
Keywords: physiological-hygienic assessment; occupational noise; operators; sensorineural deafness